Between welcome and prejudice: Experiences of gay, lesbian and bisexual university students at a community university (Revista Contexto & Educação, 2024)
The university, especially the community one, has a duty to contribute to sustainable development. Becoming more inclusive is one way to do that. Thus, from the students' point of view, the research aims to understand how the space of the community university is (or is not) a place to embrace LGBT+ students and, also, how it could be consolidated in this sense. The investigation, developed with gay, lesbian and bisexual undergraduates from a community university in southern Brazil, uses a mixed approach, carried out through a survey and interviews. Data were interpreted through the analysis of discursive practices. The results show the importance of existing supportive relationships and the positive effects of the feeling of belonging to the peer group. However, the university is not always a supportive place. Suspicious looks and hostile treatment configure microaggressions experienced in the academic environment. For the university to become more welcoming, it is necessary: the creation of collective spaces in which students feel safe and strengthened; an inclusive institutional communication; the training of the academic community for the development of cultural competence; the criticism of neutrality and the commitment to greater porosity with the sociocultural reality of the students.
Keywords: Community university; commitment to the SDGs; LGBT students; embracement